Altered Brain Function in First-Episode and Recurrent Depression: A Resting-State Functional Magnetic Resonance Imaging Study - Sun, Jifei; Chen, Limei; He, Jiakai; Du, Zhongming; Ma, Yue; Wang, Zhi; Guo, Chunlei; Luo, Yi; Gao, Deqiang; Hong, Yang; Zhang, Lei; Xu, Fengquan; et al. (Frontiers in Neuroscience, 2022)
Background: Previous studies on the differences in brain functional activity between first depressive episode (FDE) and recurrent depressive episodes (RDE) are scarce. In this study, we used regional homogeneity (ReHo) and amplitude of low-frequency fluctuation (ALFF) indexes to observe the characteristics of abnormal brain function activity and its differences between FDE and RDE patients, and to explore the correlation between abnormal brain function activity areas and clinical symptoms. Method:Twenty-nine patients with RDE, 28 patients with FDE, and 29 healthy controls (HCs) were included in the rs-fMRI scans. ReHo and ALFF metrics were used for image analysis and further analysis of the correlation between differential brain regions and clinical symptoms. Results：ANOVA showed significant differences among the three groups in ReHo and ALFF in the frontal, parietal, temporal and occipital lobes. Compared to the FDE group, ReHo was higher in the right inferior frontal triangular gyrus and lower in the left inferior temporal gyrus in the RDE group, ALFF was higher in the right inferior frontal triangular gyrus, left anterior cingulate gyrus, orbital part of the left middle frontal gyrus, orbital part of the left superior frontal gyrus and right angular gyrus and lower in the right lingual gyrus in the RDE group. Compared to the HCs group, ReHo and ALFF were lower in the left angular gyrus in the RDE and FDE groups. Pearson correlation analysis showed a positive correlation between ReHo and ALFF values in these abnormal areas in the frontal lobe and the severity of depressive symptoms (P<0.05). Abnormal brain areas in the temporal and occipital lobes were negatively correlated with the severity of depressive symptoms (P<0.05). Conclusion: Although the clinical symptoms of RDE and FDE are similar, abnormal changes in neurofunctional activity are seen in some of the same brain regions. Compared to the FDE group, ReHo and ALFF were more widely distributed in brain regions and had more complex neuropathological mechanisms in the RDE group, especially in the right inferior frontal triangular gyrus of the frontal lobe.